2006
DOI: 10.1007/s00264-006-0261-1
|View full text |Cite
|
Sign up to set email alerts
|

The functional and oncological results after scapulectomy for scapular tumours: 2–16-year results

Abstract: Twenty-five patients underwent scapulectomy for various tumours between 1989 and 2005. We describe 23 patients with scapular tumours who were followed-up for a minimum of 2 years after scapulectomy. The average age was 29 years, and two-thirds of the patients were male. Nineteen patients had malignant neoplasms, of which chondrosarcoma was most common, followed by Ewing's sarcoma. Surgical staging was by Enneking's system, with stage IIB being the most frequent. Fifteen patients underwent total scapulectomy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
49
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 13 publications
2
49
0
Order By: Relevance
“…Gibbons et al [6] reported the mean MSTS score was 71.6% in 14 cases with partial scapulectomy and concluded that the rotator cuff could be removed without a severe functional deficit provided that the deltoid was reattached to the scapular remnant and the trapezius. Mayil Vahanan et al [7] also reported partial scapulectomy in eight cases and gave superior functional results to total scapulectomy. Kapoor et al [8] concluded that no bone reconstruction was required following partial or total clavicectomy.…”
Section: Discussionmentioning
confidence: 97%
“…Gibbons et al [6] reported the mean MSTS score was 71.6% in 14 cases with partial scapulectomy and concluded that the rotator cuff could be removed without a severe functional deficit provided that the deltoid was reattached to the scapular remnant and the trapezius. Mayil Vahanan et al [7] also reported partial scapulectomy in eight cases and gave superior functional results to total scapulectomy. Kapoor et al [8] concluded that no bone reconstruction was required following partial or total clavicectomy.…”
Section: Discussionmentioning
confidence: 97%
“…Although the shoulder girdle, including the proximal humerus, the scapula and the clavicle, is the third most common site for tumours of bone and soft tissue tumours, primary tumours of the scapula still present a rare diagnosis [1][2][3][4]. Most common tumours involving the scapula are chondrosarcoma in adolescents and Ewing's sarcoma in children [3].…”
Section: Introductionmentioning
confidence: 99%
“…Most common tumours involving the scapula are chondrosarcoma in adolescents and Ewing's sarcoma in children [3]. Tumours affecting the scapula often grow quite large before being diagnosed, and during disease progression the extension of the tumour to the chest wall, the proximal humerus, the rotator cuff or the neurovascular bundle may occur [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Residual function of the affected limb tends to be minimal and unsatisfactory. Although various reconstruction techniques after total scapulectomy have been developed, such as prosthetic replacement, recycled bone grafts, or soft tissue reconstruction, the optimal reconstruction technique has not yet been determined because of the difficulties in comparing the different techniques, as the amount of remaining muscle and rotator cuff following scapulectomy varies with each surgery [5][6][7].…”
Section: Introductionmentioning
confidence: 99%